Performance Improvement of a Solar-Powered Recompression Supercritical Carbon Dioxide Cycle by Introducing an Ammonia-Water Cooling-Power System - Zhang, Yicen; Du, Yang; Lu, Xiaochen; Zhao, Pan; Dai, Yiping (Frontiers in Energy Research, 2022)
The wide utilization of solar energy is beneficial for emission reduction of carbon dioxide. This paper proposes a novel power cycle system driven by solar energy, which consists of a recompression supercritical carbon dioxide cycle (RSCO2) and an ammonia-water cooling-power cycle (ACPC). The power system operates in a ‘self-production and self-sale’ mode, which means that the refrigeration capacity produced by ACPC is utilized to cool the main compressor inlet fluid of RSCO2. The comprehensive energy and exergy analysis of proposed novel system are presented. The effects of six parameters on system thermodynamic performance are evaluated, which are direct normal irradiation, ammonia concentration of basic solution, pinch point temperature difference of evaporator, effectiveness of recuperator, pressure ratio of RSCO2 and molten salt outlet temperature. The results show that compared with the stand-alone RSCO2, the net power and energy efficiency of proposed system are improved by 15.94% and 10.61%, respectively. In addition, the increasing ammonia concentration of basic solution leads to the rise of ACPC refrigeration output, and the inlet temperature of main compressor can be declined to 32.97℃ with ammonia concentration of basic solution of 0.88. Moreover, when the effectiveness of recuperator in RSCO2 rises up to 0.98, system energy and exergy efficiencies can reach their maximum value of 30.68% and 33.10%, respectively.